2012
DOI: 10.1111/j.1365-2362.2012.02695.x
|View full text |Cite
|
Sign up to set email alerts
|

Novel dual inhibitors of vascular endothelial growth factor and VEGFR2 receptor

Abstract: Four cardiac hormones are the first dual inhibitors of VEGF and the VEGFR2/KDR/Flk-1 receptor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
21
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 23 publications
(67 reference statements)
5
21
0
Order By: Relevance
“…These four cardiac hormones decrease the VEGFR2 receptor by up to 89% in human small-cell lung cancer cells and up to 92% in human prostate cancer cells (Nguyen et al 2012). These results were confirmed by Western blot that revealed a cardiac hormone-mediated decrease in VEGFR2 receptor (Nguyen et al 2012).…”
Section: Vascular Endothelial Growth Factorsupporting
confidence: 72%
See 2 more Smart Citations
“…These four cardiac hormones decrease the VEGFR2 receptor by up to 89% in human small-cell lung cancer cells and up to 92% in human prostate cancer cells (Nguyen et al 2012). These results were confirmed by Western blot that revealed a cardiac hormone-mediated decrease in VEGFR2 receptor (Nguyen et al 2012).…”
Section: Vascular Endothelial Growth Factorsupporting
confidence: 72%
“…The four cardiac hormones maximally decrease the VEGFR2 receptor in human pancreatic adenocarcinoma cells up to 83% (Nguyen et al 2012). These four cardiac hormones decrease the VEGFR2 receptor by up to 89% in human small-cell lung cancer cells and up to 92% in human prostate cancer cells (Nguyen et al 2012).…”
Section: Vascular Endothelial Growth Factormentioning
confidence: 99%
See 1 more Smart Citation
“…After binding to their respective receptors on the tumor cells, all the four natriuretic peptides inhibit some metabolic targets including the GTPase RAS [21], the MEK1/2 kinase [22] and the extracellular signal-regulated kinase (ERK) 1/2 [23]. In addition to its ability of inhibiting the Ras-MEK1⁄2-ERK1⁄2 kinase cascade, functioning as a multikinase inhibitor, it has been recently reported that ANP (as well as the other three natriuretic hormones) is able to decrease, in tumor cells, the levels of vascular endothelial growth factor (VEGF) and its main receptor VEGFR2 [24], and of the Signal Transducer and Activator of Transcription 3 (STAT 3)[25], that are three molecular targets useful for cancer therapy [26-28]. Moreover, owing the observed localization of ANP in the nuclear compartment of human pancreatic adenocarcinoma cells, a direct interaction of the peptide with growth-promoting hormones in the nucleus has been hypothesized [29].…”
Section: Mechanism(s) Of Action Of Anp: Specific Receptors and Metabomentioning
confidence: 99%
“…88 These 4 cardiac hormones also decrease VEGF’s concentrations up to 58%. 88 These cardiac hormones are, thus, the first dual inhibitors of VEGF and its R2 receptor, as there are no compounds that inhibit both, although there are compounds that inhibit VEGF and other compounds that inhibit the VEGFR2 receptor. 88 …”
Section: Ras-mek 1/2 - Erk 1/2 Kinase Cascadementioning
confidence: 99%